(untitled) (Eurasian Journal of Philology Science and Education, 2019)
Kairat Zhumagaliyev is one of the first names that are mentioned among the poets who ascended to the height of Kazakh lyrics since he has displayed his inner world and his mastery in all kinds and genres of lyric poetry. Most of his creative heritage consists of both poems and ballads and lyrical works. Thematic scope of K. Zhumagaliyev’s poems is various. At the earlies stage of his creative work he was more inclined to children’s poetry and later he started to develop into a poet having a mature civic position. He intentionally began to choose social and political themes. Having improved his artistic mastery, he gradually proceeded to glorification of national spiritual values of his people. Touching upon a subject that is so cherished and near to heart and conscience of the nation, the poet K. Zhumagaliyev naturally fosters in his readers careful attitude to spiritual values. His poetic creations have an important peculiarity – the poet glorifies national character, national spirit and national identity. The poet recalls with respect the great warriors-defenders of the steppe whose military work and feats are an inexhaustible source of inspiration for future generations. The poet had to work hard in order to impart to future generation in an accessible form and in detail historical events that took place in life of the Kazakh people, the master of the boundless steppes. The poet wants with all his heart that his independent people always remember the names of those who have left an outstanding mark in the history of the country. Based on numerous historical facts, Zhumagaliyev describes them from the point of view of the spectator in order to reconstruct pictures of events and actions performed for the welfare of the nation. The tradition of the Kazakh people’s hospitality is one of the basic themes of his poetry. In his poems the poet describes truthfully and without bias modern manifestation of traditions handed down from generation to generation. Such themes as respect for elders, concern for the younger are particularly topical to the works of the poet Kairat Zhumagaliev. These virtues are part of and attributes of folk pedagogy, the attitude of modern society to old but ever-young values. The article reveals the theme, the ideological goal of the poet in glorifying spiritual values. Using scientific and literary analysis it forms the rationale for the poet’s ability to convey a strong connection between the past and the present of the people, to show events of the long-ago through the prism of the worldview of modern man.